PERKUATAN LERENG DENGAN GEOGRID DAN SHEET PILE PADA JALAN KIKIM BESAR (KM. 256) KOTA LAHAT - Hastuti, Yulia; Wahyuni, R.A. Mitha; Dewi, Ratna (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2016)
Landslide is one of the most common problems in improving road structures. One of the landslide cases occurred in the area of Kikim Besar, Lahat District precisely at Km.256. To obtain an optimal solution of the problem requires proper analysis in the reinforcement of the slope. In this study used an alternative slope reinforcement by using sheet pile or geogrid reinforcement. The purpose of this research is to know the condition of natural slope stability at that location and the effect of stability slope change with retrofitting structure using sheet pile or geogrid. This research uses modeling with Plaxis 2D program. Modeling was made to obtain the safety factor values on the natural slopes on the slopes 1-1, 2-2, and 3-3 pieces, comparing the safety factor of each slope before and after the reinforcement, and comparing the safety factor of each slope after reinforcement using geogrid type UX 1700 and sheet pile type W325 A 1000. From the research results obtained that the strengthening of geogrid and sheet pile can increase the value of slope safety factor. The sheet pile modeling has the greatest safety factor value for each slope of 1.794 for slopes 2-2 and 1,532 for slopes 3-3 compared with geogrid reinforcement that produces a safety factor value of 1,325 for slopes 2-2 and 1,343 for slopes 3-3 pieces.